Estudo de adsorção de íons crômio em bentonita aminofuncionalizada - Gilberto, Thales Jati (2013)
Bentonite is a clay mixture widely employed in adsorption studies due to its advantageous characteristics such as: a good capacity of cationic exchange, an elevated superficial area, porosity and possibility of intercalation and/or functionalization of diverse substances. The present paper’s main objective, is to study the functionalization with alkoxides organically modified in the inorganic matrix (bentonite) in order to produce hybrid materials with desirable properties for adsorption studies. Therefore, in this study, the alkoxides (3-aminopropyl) triethoxysilane (APTS), (trimethoxisilil) propylethylenediamine (TMPO), (N1 (trimethoxysilylpropyl) dietiylentriamina) (TMPT), the resulting materials were denominated Ben-APTS, Ben-TMPO and Ben-TMPT. The materials were characterized through absorption spectroscopy in the infrared region, x-ray diffractometry, thermal analysis, superficial area analysis and adsorption experiments with methylene blue to determine the cationic exchange capability.. Evidence of the functionalization of Bentonite were obtained through characterization techniques such as XRD, FTIR, TG, SEM e BET. Adsorption of chromium ions were also performed to determine the optimum time of adsorption isotherms and their the matrices with improved adsorption of hybrid materials.